2016
DOI: 10.18632/oncotarget.8040
|View full text |Cite
|
Sign up to set email alerts
|

FAK and paxillin, two potential targets in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a devastating cancer in large part due to late diagnosis and a lack of effective screening tests. In spite of recent progress in imaging, surgery and new therapeutic options for pancreatic cancer, the overall five-year survival still remains unacceptably low. Numerous studies have shown that focal adhesion kinase (FAK) is activated in many cancers including PDAC and promotes cancer progression and metastasis. Paxillin, an intracellular adaptor protein that plays a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 152 publications
(137 reference statements)
1
74
0
1
Order By: Relevance
“…were validated by analyzing the expression of several rPaC-related proteins, including ITGA3, Src, FAK, and Rac. These proteins had been reported activated in the progression and metastasis of PaC (Kanteti, Batra, Lennon, & Salgia, 2016;Razidlo et al, 2015;Xu, Wang, An, & Xu, 2013), which also supported our results. And we further verified PaC cells transfected with ITGA2 and miR-107 inhibitors could stimulate the expression of those proteins.…”
Section: Discussionsupporting
confidence: 93%
“…were validated by analyzing the expression of several rPaC-related proteins, including ITGA3, Src, FAK, and Rac. These proteins had been reported activated in the progression and metastasis of PaC (Kanteti, Batra, Lennon, & Salgia, 2016;Razidlo et al, 2015;Xu, Wang, An, & Xu, 2013), which also supported our results. And we further verified PaC cells transfected with ITGA2 and miR-107 inhibitors could stimulate the expression of those proteins.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have revealed that FAK is a key molecule for cell proliferation, migration, and invasion during cancer progression . Focal adhesion kinase has also been shown to be upregulated in many cancers, including OS .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that FAK is a key molecule for cell proliferation, migration, and invasion during cancer progression. (20)(21)(22)(23) Focal adhesion kinase has also been shown to be upregulated in many cancers, including OS. (13) Ren et al reported that p-FAK (Y397) was highly expressed in 37% of primary human OS tissues (42/113) and greater p-FAK (Y397) overexpression was associated with more aggressive OS and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of the patients with higher PAX expression was poorer than those with low expression of PAX [6]. PAX, which is an intracellular adaptor protein, plays a basic role in the organization of the cytoskeleton, this connects integrins to FAK and plays an important role in both the assembly and disassembly of focal adhesions [7]. Overexpression of FAK as well as overexpression of CD98 and β1 and β3 integrins was found to be associated with the progression of colon carcinoma and its liver metastases [8] while GPR56 was only just recently studied by Sewda et al [9] who have found that GPR56 expression was significantly correlated with the proximal tumor location and with the expression of mismatch repair genes.…”
Section: Introductionmentioning
confidence: 99%